2016
DOI: 10.1371/journal.pone.0148139
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Doses of Temozolomide Enhance the Efficacy of Carbon Nanotube CpG Immunotherapy in an Invasive Glioma Model

Abstract: Even when treated with aggressive current therapies, most patients with glioblastoma survive less than two years. Rapid tumor growth, an invasive nature, and the blood-brain barrier, which limits the penetration of large molecules into the brain, all contribute to the poor tumor response associated with conventional therapies. Immunotherapy has emerged as a therapeutic approach that may overcome these challenges. We recently reported that single-walled carbon nanotubes (SWCNTs) can be used to dramatically incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…Similar results have been reported in the study by Ouyang et al, in which SWCNTs were administered in combination with TMZ; the authors attributed this effect to immune modulation, potentiation of TMZ and the covering of nanotubes with oligodeoxynucleotides CpG. 42 It is important to consider that the effect of CNTs is dependent on intrinsic factors such as formulation, production and endocytosis capacity. 38 This investigation evaluated the effect of the MWCNTs plus TMZ in malignant glial cells and MWCNTs bioavailability in RG2 glioma cells: functionalized MWCNTs were more efficiently endocytosed by RG2 cells than nonfunctionalized MWCNTs.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results have been reported in the study by Ouyang et al, in which SWCNTs were administered in combination with TMZ; the authors attributed this effect to immune modulation, potentiation of TMZ and the covering of nanotubes with oligodeoxynucleotides CpG. 42 It is important to consider that the effect of CNTs is dependent on intrinsic factors such as formulation, production and endocytosis capacity. 38 This investigation evaluated the effect of the MWCNTs plus TMZ in malignant glial cells and MWCNTs bioavailability in RG2 glioma cells: functionalized MWCNTs were more efficiently endocytosed by RG2 cells than nonfunctionalized MWCNTs.…”
Section: Discussionsupporting
confidence: 80%
“…While the KR158 malignant glioma model used here is highly invasive [37], numerous clinical trials testing delivery strategies to improve distribution of therapeutics in the brain [33, 38] have highlighted the difficulty with translating results from smaller pre-clinical models to humans. In the future, we plan to test this therapeutic formulation strategy in larger mammals (pigs and tumor-bearing dogs) in order to better understand critical limitations to human translation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrated that CNTs could improve CpG uptake into tumor-associated inflammatory cells without toxicity and lead to a robust antitumor response. Recently, Ouyang et al 115 proposed an SWCNT complex that increased the immunotherapeutic efficacy of CpG ODNs. SWCNT-CpG was combined with temozolomide and evaluated in an invasive mouse glioma model (K-Luc) that better recapitulates human disease.…”
mentioning
confidence: 99%